Rapidly rotating condensates in a bubble trap - Sousa, Guilherme Tomishiyo Teixeira de (2022)
We study a rotating Bose-Einstein Condensate (BEC) trapped in a shifted harmonic oscillator and Mexican Hat trap, which approximates the potential of a bubble trap potential in some situations. We determined the vortices configurations that appears in this system by varying the interaction and angular momentum of the atomic cloud. The system phase diagram has the macrovortex configurations for small values of the interaction parameter. The charge of the central vortex increases with increasing rotation. Higher values of the atomic interaction turns the macrovortex unstable. It decays into multiple single-charged vortices that arrange themselves in a lattice. Since the vortices are not always visible in the absorption images, we look for alternative methods to characterize the vortex configuration. More specifically, we search for experimental signatures to determine the transitions in the phase diagram. For that, we study how the BECs velocity field affects the collective modes of the condensate. The splitting of the modes degenerescence and the increase in the mode frequency with angular velocity, which can be traced to a reduction in the gas compressibility, can be seen as an indirect signature of the presence of the vortices in the trapped BEC.